ANALISIS EKOKRITIK DALAM NOVEL KEKAL KARYA JALU KANCANA - Apriyanti Sihotang; Een Nurhasanah; Slamet Triyadi (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2021)
This research is motivated by the amount of environmental damage that occurs and the lack of understanding of the position of humans with the natural environment, this study aims to build awareness to care for the universe so that it can form a generation that cares and loves its environment. This study describe (1) the intrinsic elements of the novel Kekal by Jalu Kancana, (2) the environmental crisis in the novel Kekal by Jalu Kancana with an ecocritical approach. This study uses an approach with descriptive analysis method, which presents facts in the form of descriptions. The theory used in this research is Nurgiyantoro's intrinsic theory and literary ecocriticism, Greg Garrard's environmental crisis. The subject of this research is the novel Kekal by Jalu Kancana, the object of this research is the intrinsic elements and forms of environmental crisis in the novel Kekal by Jalu Kancana. The results of this study are: (1) intrinsic theory of the novels include the theme of environmental damage; a plot divided into five stages; characters and characterizations include Alit, Pepep, Tama, Alit's father, Mr. Murat, Kastia, Riski, Triyogo and Hassan; the background consists of place setting, namely Bandung and the area on the island of Sumatra, time setting (Morning, Afternoon, Evening, Four years ago, September, 2017), socio-cultural background (life habits of people who do not take care of the natural environment); the point of view of the main character's